The Social Capital as a Security Factor - Popova, Zora (Journal of Regional Security, 2018)
The paper focuses on the role of social capital reconstruction after an ethnic conflict, addressing the importance of citizenship (re-)building for the political and economic development. Exploring the lessons learned from Bosnia and Herzegovina, the paper identifies several levels, at which policy efforts should be directed in order to ensure achievement of expected outcomes. Social capital is a complex mechanism that enables coherence and functioning of any societal system and especially of a state. If elements of social capital do not match, if the macro-level of social capital does not embrace a relevant micro-level, the system is in risk of failure and collapse. When a social capital of a political unit (e.g. state) is in focus, it could be regarded as a security factor. The findings can be applied to assess developments and to evaluate the stability risk in newly emerging states and countries in transition to democracy.